Framework for Object Oriented WWW Applications using Embedded Concepts - Chagi, A (International Journal of Computer Sciences and Engineering, 2025)
We present the design of a C++ framework for building custom Web agent applications. Our framework includes abstractions for networking and communications as well as a format-independent set of classes for representing document components. We discuss the design and parts of the implementation of the framework and present possible extensions till date.